Teacher Quality Affects On Graduation Of Study Programming Data Approach There With CRISP-DM Method - Harahap, Mawaddah; Hidayati, Namira; Panjaitan, Sumiati; Tambunan, Enjelyna; Sihombing, Juniati (Politeknik Ganesha Medan, 2023)
Each student's graduation is influential to the teacher in every subject that can be predicted based on the pattern of habits of the teacher who presents the subject. Web Proggramming is the subject of study that must be completed by every student. If this course is not completed, it is not allowed for the student to take other courses related to it. The custom patterns of teachers in this study were taken from 300 student respondents. An analysis is done to compare the results of questionnaire scores with the assessment of college admissions teachers. From the results of the comparison, it is possible to predict the graduation rate of students to the web programming course. The results of the experiment were that 72% of the students received highly influential predictions, 12% Influential, 7% Sufficient, 5% Influential and 4% Highly Influential.